The Collapse of Democratic Regimes: the Construction of Juan Linz’s and Alain Touraine’s interpretations - Makino (PPGCEPPAC/UnB), Rogério (Instituto de Ciências Sociais da Universidade de Brasília, 2014)
The fall of democratic regimes was widely common in the political history of many Latin American countries in the second half of the twentieth century. This essay analyzes the construction of the conceptual and interpretative framework from two important authors who study the subject (Juan J. Linz and Alain Touraine), emphasizing their convergences.